PEMBERDAYAAN DALAM RANGKA PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH PEMBUATAN TAHU - Nuruddin Mahmud; Akhmad Nurrofi; Bayu Teguh Wibowo; Antonius Along (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Home Industries are considered to able to boost national economc growth by strengthening regional economie,. The MSME partnering in this community service activity is a tofu-making MSME located in Bangkung Village, Mranggen District, Demak Regency. Some of the challenge faced by this MSME iclude Traditional management and a leck of marking innovation.The Method used to address thesse parthers’challenges is interviews and trainingconductet through shareng. The goal of this activity is to provide an understandding of the importance of innovation and good businessmanagement to enable business to grow.The resultsof this community service activity include business permist, product inovation ideas, and the provision of medicine.